Automação no processo de pintura aeronáutica como alternativa na sustentabilidade ambiental - Menezes, Eliud Rodrigues (Universidade Federal de São Carlos, 2021)
Sustainability in industrial processes is a requirement in accordance with environmental legislation, in addition to being a competitive strategy for organizations, since it minimizes solid waste and there is economical resources, among others. In the aeronautical sector there are several processes that can be applied to the concepts of sustainability, and one of the processes is the preparation and painting of aircraft generates solid residues, liquid effluents and atmospheric emissions. In addition to causing environmental impacts, the generation of waste represents waste of raw material and energy and requires high investments in pollution control and treatment techniques. Given this context, the general object of this work was to analyze the process in an industrial painting booth in the aeronautical sector and as a specific objective to implement improvements in this process through industrial automation, aiming at process efficiency and environmental sustainability. The research was based on a Case Study of the painting process of an aeronautical industry. The main results were: a 65% reduction in solid waste, a 60% reduction in water consumption, a 40% reduction in the emission of gases into the atmosphere, minimization of sick leave due to occupational diseases with zero sick leave.
Automation in the aeronautical painting process as an alternative in environmental sustainability
Keywords: Automação industrial; Balanço hídrico; Emissões atmosféricas; Impactos ergonômicos; Processo de pintura; Resíduos sólidos; Industrial automation; Hydric balance; Atmospheric emissions; Ergonomic impacts; Painting process; Solid waste; ENGENHARIAS